Physical activity and health behaviors of children from 4-6 classes of primary school living in the villages of the Lublin and Lodz voivodeships. - Jankowska, Paula; Rudnicka-Drożak, Ewa (Journal of Education, Health and Sport, 2018)
Introduction Health behaviors shape throughout life. The family is the first educational environment of the child, in which health habits are created. Nutrition and nutritional status in childhood and early adolescence determine the health of an adult person to a large extent. Lack of physical activity can bring with it many negative effects, including overweight and obesity in children, metabolic syndrome, lack of motor coordination. Objective The aim of the study was to assess health awareness and attitudes of children from classes IV-VI of rural primary schools in the Lublin and Lodz voivodeships. Material and methods The study group consisted of 65 children from classses 4 to 6 attending primary schools in the Lublin and Łódź voivodships. There were 34 girls and 31 boys among the respondents. The diagnostic survey method used a questionnaire constructed by the authors. The obtained results were statistically analyzed using the STATISTICA 12.5 program. Results Only 43.08% of respondents ate 5 recommended meals. As many as 55.38% of children ate sweets several times a week, and 7.69% - every day. 66.15% of respondents stated that they consumed fresh vegetables and fruits every day, and 24.62% - several times a week. The vast majority of children ate breakfast before going to school (73.85%). A very worrying fact is that over a quarter of children’s physical activity was limited to physical education only. Children assessed their knowledge of the principles of a healthy lifestyle: 23.08% - great, 53.85% - good, 20% - average and 3.08% poor. Conclusions Sweats and sweet drinks were disturbingly common in children’s diets. The frequency of children’s consumption of fresh vegetables and fruits could be described as satisfactory. An important problem was the low physical activity.